The twin foci of organisational identification and their relevance for commitment: a study of marketing communications industry - Podnar, Klement; Golob, Urša (Journal of Business Economics and Management, 2014)
The purpose of this paper is to distinguish the two foci of organisational identification and to explore relations among employees’ groups and corporate identification, perceived external prestige, and organisational commitment. Structural equation modelling was applied to data collected by questionnaire from a sample of 145 respondents employed in advertising agencies, to test the relationships between the researched concepts. Organisational identification comprises identification with the organisation both as a collective of individuals and as a social entity. Perceived external prestige augments corporate identification and helps to explain organisational commitment. A strong positive link between corporate identification and organisational commitment was also found. The findings suggest a means for marketing strategists and general managers to predict the consequences of managing reputation for employees and to undertake appropriate initiatives to enhance corporate identification inside the company and thus influence organisational commitment and corporate performance.